Landscapes and Landforms of Terrestrial and Marine Areas - Soldati, Mauro; Foglini, Federica; Prampolini, Mariacristina; Savini, Alessandra (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This volume collects papers dealing with the integrated study of emerged and submerged areas, by means of different approaches and techniques. It shows the reasons why the integration of terrestrial and marine datasets would be desirable in geoenvironmental studies, and demonstrates how such an integration is unquestionably beneficial in modern research, ranging from Late Quaternary landscape evolution to geohazards, geomorphological mapping, geoarchaeology, geoheritage and geodiversity, and marine benthic habitat mapping.